2009
DOI: 10.1007/s12011-009-8458-y
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Seleno-l-Methionine on Cyclophosphamide-Induced Urinary Bladder Toxicity in Rats

Abstract: Cyclophosphamide (CP) is a widely used antineoplastic drug, which could cause toxicity of the normal cells due to its toxic metabolites. Its urotoxicity may cause doselimiting side effects like hemorrhagic cystitis. Overproduction of reactive oxygen species (ROS) during inflammation is one of the reasons of the urothelial injury. Selenoproteins play crucial roles in regulating ROS and redox status in nearly all tissues; therefore, in this study, the urotoxicity of CP and the possible protective effects of sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
(40 reference statements)
1
8
0
Order By: Relevance
“…23 In addition, CYP-induced HC causes ROS overproduction, which leads to oxidative stress, peroxidation of lipid and loss of protein activities ultimately. 25,54,55 Moreover, another study indicated that glutathione has similar protective efficiency compared with mesna. It is worth to mention that mesna can only be used in CYP-induced HC because it may cause allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 In addition, CYP-induced HC causes ROS overproduction, which leads to oxidative stress, peroxidation of lipid and loss of protein activities ultimately. 25,54,55 Moreover, another study indicated that glutathione has similar protective efficiency compared with mesna. It is worth to mention that mesna can only be used in CYP-induced HC because it may cause allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 A few studies described the protective effects of antioxidants, especially sulfhydryl-containing compounds, on CYP-induced HC. 25,54,55 Moreover, another study indicated that glutathione has similar protective efficiency compared with mesna. 56 These findings lead us to further investigate the effects of antioxidant and mesna to CYP-induced HC.…”
Section: Discussionmentioning
confidence: 99%
“…ere are numerous reports documenting the role of NO in CP-induced HC [6,9,28]. Additionally, it has been shown that bladder damage may be due not only to the overproduction of NO but also of ROS [29][30][31]. It is well known that reactions of ROS with biomolecules such as lipids can initiate chain reactions and lead to tissue damage [32].…”
Section: Discussionmentioning
confidence: 99%
“…CP has been associated with various kinds of urinary tract toxicities [20,21], but kidney toxicity has only rarely been reported. necrosis had developed after a single i.p.…”
Section: Discussionmentioning
confidence: 99%